To find the amount of change Layla receives, we can start from the transaction where she gives the cashier $50 for the shoes that cost $40.99. The change can be calculated by subtracting the cost of the shoes from the amount paid.
The equation that represents this situation is:
Change = Amount given - Cost of shoes
So in this case:
Change = 50 - 40.99
Now we can calculate the change:
Change = 50 - 40.99 = 9.01
Thus, Layla will receive $9.01 in change.
Now let's look at the options you provided:
- AC (−40.99) = 50: This does not correctly represent the change calculation.
- BC (−50) = 40.99: This expression is also incorrect for calculating change.
- CC + 50 = 40.99: This equation doesn't make sense as it does not follow logically from the transaction.
- DC + 40.99 = 50: This equation can be rearranged to solve for change (i.e., Change = 50 - 40.99), which correctly calculates to $9.01.
The correct way to express the equation should be more straightforward as:
Change = 50 - 40.99
Therefore, Layla receives $9.01 in change.